2006
DOI: 10.1152/ajprenal.00234.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor-23 increases mouse PGE2production in vivo and in vitro

Abstract: Fibroblast growth factor-23 (FGF-23) has been implicated in the renal phosphate wasting in X-linked hypophosphatemia, tumor-induced osteomalacia, and autosomal dominant hypophosphatemic rickets. Recently, we demonstrated that Hyp mice have greater urinary PGE2 levels compared with C57/B6 mice and that indomethacin administration in vivo and in vitro ameliorates the phosphate transport defect in Hyp mice. To determine further whether altered prostaglandin metabolism plays a role in the renal phosphate transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Similarly as described for the PTH-induced signaling pathway (see above), the action of FGF-23 was blocked by inhibitors of ERK1/2. In addition, in isolated proximal tubules, FGF-23 was reported to provoke an increase of the production of prostaglandin PGE2 that was also suggested to occur via the MAPK/ERK pathway [111].…”
Section: Phosphatoninsmentioning
confidence: 98%
“…Similarly as described for the PTH-induced signaling pathway (see above), the action of FGF-23 was blocked by inhibitors of ERK1/2. In addition, in isolated proximal tubules, FGF-23 was reported to provoke an increase of the production of prostaglandin PGE2 that was also suggested to occur via the MAPK/ERK pathway [111].…”
Section: Phosphatoninsmentioning
confidence: 98%
“…PGE 2 also reduces phosphate transport in mouse proximal convoluted tubules. 7 Though very little is known about PT salt and water transport in response to PGE 2 , a recent study by Herman et al 8 describes a mechanism involving both protein kinase C and cAMP, by which PGE 2 regulates Na + -K + -ATPase in primary cultures of rabbit renal PT cells. PGE 2 can also mediate the responses of other hormonal systems on PT sodium transport function.…”
mentioning
confidence: 99%
“…3) [66]. Furthermore, proximal tubules incubated in vitro with arachidonic acid showed that Hyp mice had greater rates of PGE 2 production than control mice [67]. Injection of FGF-23 into control mice resulted in an increase in PGE 2 excretion, and incubation of proximal tubules with FGF-23 increased the rate of PGE 2 production to levels comparable to those seen in Hyp mice (Fig.…”
Section: Pge 2 Production In Hyp Micementioning
confidence: 70%